Epidemiological research terms and concepts - Miettinen, Olli S. (Olli Sakari) 1936- (Springer, 2011)
This book is by a single author ? someone who, after medical school, has devoted half-a-century of full-time effort to ever better understand both clinical and community medicine and the research that is needed to produce the scientific knowledge-base of these.  The book is organized so as to address in separate sections first the preparatory topics of medicine (clinical and epidemiological), science in general, and statistics (mathematical); then topics of epidemiological research proper; and, finally, topics of ?meta-epidemiological? clinical research.  In those two main sections, a further grouping is based on the distraction between objects and methods of study.  In this framework, the particular topics are addressed both descriptively and quasi-prescriptively, commonly with a number of explicatory annotations. This book is intended to serve and a handbook for whomever is, in whatever way, concerned with epidemiological or ?meta-epidemiological? clinical research.  But besides, it is intended to serve as a textbook for the students in introductory courses on ?epidemiological? research ? to which end there is a suggested hierarchy of the concepts that might reasonably be cover